2020
DOI: 10.3126/jiaas.v36i1.48388
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield and Agro-Climatic Indices of Rice Cultivars Transplanted in Different Dates in Mid-Western Tarai, Nepal

Abstract: An experiment was conducted to assess the productivity and agro-climatic indices of different rice cultivars under staggered transplanting dates in farmers’ field at Lamahi, Dang during May to November 2018. The experiment was laid in a two factorial randomized complete block design with 9 treatments and 3 replications. Two factors included were: three rice cultivars; Arise-6444, Sarju-52, and Sukkha-3, and three transplanting dates; 19th June, 29th June, and 9th July. Phenological observation and yield attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Similarly, Peng-fei et al [19] observed a linear negative association between sowing time and growth period. The findings of the present study were also similar to those reported by Bhandari et al [20] and Hussain et al [21].…”
Section: Phenological Parameterssupporting
confidence: 93%
“…Similarly, Peng-fei et al [19] observed a linear negative association between sowing time and growth period. The findings of the present study were also similar to those reported by Bhandari et al [20] and Hussain et al [21].…”
Section: Phenological Parameterssupporting
confidence: 93%